Histone chaperone FACT complex mediates oxidative stress response to promote liver cancer progression. Issue 2 (22nd August 2019) - Shen, Jialing; Chen, Mengnuo; Lee, Derek; Law, Cheuk-Ting; Wei, Lai; Tsang, Felice Ho-Ching; Chin, Don Wai-Ching; Cheng, Carol Lai-Hung; Lee, Joyce Man-Fong; Ng, Irene Oi-Lin; Wong, Carmen Chak-Lui; Wong, Chun-Ming
Abstract : Objective: Facilitates Chromatin Transcription (FACT) complex is a histone chaperone participating in DNA repair-related and transcription-related chromatin dynamics. In this study, we investigated its oncogenic functions, underlying mechanisms and therapeutic implications in human hepatocellular carcinoma (HCC). Design: We obtained HCC and its corresponding non-tumorous liver samples from 16 patients and identified FACT complex as the most upregulated histone chaperone by RNA-Seq. We further used CRISPR-based gene activation and knockout systems to demonstrate the functions of FACT complex in HCC growth and metastasis. Functional roles and mechanistic insights of FACT complex in oxidative stress response were investigated by ChIP assay, flow cytometry, gene expression assays and 4sU-DRB transcription elongation assay. Therapeutic effect of FACT complex inhibitor, Curaxin, was tested in both in vitro and in vivo models. Results: We showed that FACT complex was remarkably upregulated in HCC and contributed to HCC progression. Importantly, we unprecedentedly revealed an indispensable role of FACT complex in NRF2-driven oxidative stress response. Oxidative stress prevented NRF2 and FACT complex from KEAP1-mediated protein ubiquitination and degradation. Stabilised NRF2 and FACT complex form a positive feedback loop; NRF2 transcriptionally activates the FACT complex, while FACT complex promotes the transcription elongation of NRF2 and its downstream antioxidant genes through facilitating rapid nucleosome disassembly for the passage of RNA polymerase. Therapeutically, Curaxin effectively suppressed HCC growth and sensitised HCC cell to sorafenib. Conclusion: In conclusion, our findings demonstrated that FACT complex is essential for the expeditious HCC oxidative stress response and is a potential therapeutic target for HCC treatment.